Accelerated development programmes for Black academics: Interrupting or reproducing social and cultural dominance? - Booi, Masixole (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2016)
A wide body of research literature on transformation of higher education institutions in South Africa has focused on institutional reform and restructuring, change in employment legislation and policies, transforming institutional culture(s) and student and staff demographics (Portnoi, 2009:373; Viljoen and Rothmann, 2002:3; Badat, 2007; 2010; Cloete, Muller, Makgoba and Ekong, 1997; Nieman, 2010). The literature on transformation of higher education institutions shows that the underrepresentation, recruiting and retaining of blacks and women in senior posts is still the major challenge faced by the project of transforming higher education, particularly in Historically White Institutions (HWIs). Universities have introduced a variety of 'accelerated development' programmes to meet this challenge and accelerate the entry into academia of black academics. The present study draws on Pierre Bourdieu's notions of cultural capital, field and social capital to interpret the lived experiences of participants in the Accelerated Development Programme (ADP) of one HWI. In particular the study is interested in how, in the participants' experience, they, as members of the programme, have or have not been able to contribute to the transformation of the culture(s) of the institution. The study critically examines the assumption that the institutional practices, values and norms can be changed only by socialising 'new' lecturers into an already existing dominant culture rather than seeing the need to socialise existing lecturers into a new culture informed by a democratic ethos.
Keywords: Uncatalogued